The acquisition of Focus in L2 Spanish - Leal, Tania; Destruel, Emilie; Hoot, Bradley (Second language research, 2019)
This paper examines the strategies used by speakers of Spanish as a second language (L2) for marking Information Focus, a phenomenon found at the syntax–discourse interface. Sorace and colleagues have proposed the Interface Hypothesis, according to which the syntax–discourse interface poses unique challenges for bilinguals (Sorace, 2011). With respect to Spanish, there exists a gap between the theoretical and empirical literatures on Focus realization; the former suggests that Focus must appear in sentence-final position, yet recent experimental work challenges this claim, showing that Focus commonly remains in situ. Using a speeded production task, we compared the response patterns of L2 Spanish speakers to that of natives in order to bring additional evidence to bear on the debate. Results revealed an asymmetry: L2 learners converged with native speakers on Subject Focus but not on Object Focus, where proficiency mediated overall divergences, indicating a change toward more nativelike Focus-marking strategies over time. We discuss our findings in light of the Interface Hypothesis and existing theories of Focus marking in Spanish.